Pengaruh Kepemimpinan Perempuan Terhadap Sistem Pendidikan di SD Islam Integral Luqman Al-Hakim 02 Batam - Juni Mahnis; Nadila Nadila (TADRIBUNA, 2021)
This type of research is a quantitative descriptive approach. The population of this research is teachers and some staff in schools. While the sample uses a non-probability sampling technique, namely census or saturated sample. The data is collected through observation, interviews, questionnaires and documentation. The researcher's data analysis technique used a prerequisite test, namely normality and hypothesis testing, namely a simple linear regression test to see the effect of the X variable on Y. The results of the study indicate that there is an influence of women's leadership on the system of educational. It was found that the t count was 10,881 with a significant level of 0.000, because sig. <0.05 then Ho is rejected, which means that women's leadership affects the educational system system. Then it is known that the influence of women's leadership on the system of educational institutions is 80,9%, and the rest is influenced by other factors..